The philosophy of history - Hegel, Georg Wilhelm Friedrich (Dover Publications, Inc., 1956)
Introduction to the Philosophy of History is a short posthumous publication of Hegel's lecture notes pertaining to the nature of history (There are several similar publications of Hegel notes, e.g. The History of Philosophy, The Philosophy of Art. Georg Hegel was one of the most popular and influential German idealists of the ninetieth century. This short book (approximately 100 pages also includes an excerpt from the The Philosophy of the Right.